Teachers and Learners’ Perceptions about Implementation of AI Tools in Elementary Mathematics Classes - Xuejing Song; Joonkong Mak; Haowei Chen (SAGE Open)
The integration of artificial intelligence (AI) tools in educational environments presents creative chances to improve mathematics education in elementary schools. This mixed-method study investigates the use of artificial intelligence tools in elementary mathematics classrooms. Complementing qualitative data from semi-structured interviews, the study had a quasi-experimental design with pre-and post-tests to measure students’ mathematical skills and a survey to explore perceptions about AI-based tool implementation. Following the employment of artificial intelligence tools, quantitative data show a notable increase in learners’ general mathematics performance and problem-solving ability. Qualitative data provide a deep insight of teachers and learners understanding about AI tools utilization in elementary mathematics classrooms and personalized experiences with expectations for learning process. Apart from several advantages, the findings highlighted few reservations about technological issues and ethical privacy concerns. However, the data analysis concludes AI tools implementation visibly enhance elementary mathematics classroom performance with the help of appropriate technology training and reasonable resources. This study advances knowledge on how best to include artificial intelligence into the classroom thereby augmenting instruction and learning support. The findings also lead to future recommendations for further research considering gender differences, bigger sample and different demographic regions.